2022
DOI: 10.3390/cancers14030723
|View full text |Cite
|
Sign up to set email alerts
|

MR Fingerprinting—A Radiogenomic Marker for Diffuse Gliomas

Abstract: (1) Background: Advanced MR imaging (MRI) of brain tumors is mainly based on qualitative contrast images. MR Fingerprinting (MRF) offers a novel approach. The purpose of this study was to use MRF-derived T1 and T2 relaxation maps to differentiate diffuse gliomas according to isocitrate dehydrogenase (IDH) mutation. (2) Methods: Twenty-four patients with histologically verified diffuse gliomas (14 IDH-mutant, four 1p/19q-codeleted, 10 IDH-wildtype) were enrolled. MRF T1 and T2 relaxation times were compared to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 50 publications
1
15
0
1
Order By: Relevance
“…Along with others, we have reported that the T1- and T2-relaxation properties of tumor tissue tightly correlate with the IDH mutation status of LrGGs 16 , 27 . These observations were obtained either by employing conventional MR relaxometry techniques 16 , 28 or by newly developed magnetic resonance fingerprinting technology 29 .…”
Section: Discussionsupporting
confidence: 72%
“…Along with others, we have reported that the T1- and T2-relaxation properties of tumor tissue tightly correlate with the IDH mutation status of LrGGs 16 , 27 . These observations were obtained either by employing conventional MR relaxometry techniques 16 , 28 or by newly developed magnetic resonance fingerprinting technology 29 .…”
Section: Discussionsupporting
confidence: 72%
“…More recent studies have addressed the role of multi‐echo SE T2 mapping in IDH mutation status of adult LGGs and showed an increase in T2 in IDH‐mutant glioma compared to IDH‐wildtype glioma 109 . This was also observed in an MRF study, which showed an increase in T1 values in the solid component of IDH mutant glioma, compared to wildtype 112 . An example of these findings is displayed in Fig.…”
Section: Resultsmentioning
confidence: 54%
“…The MRF T1 map ( c ) and T2 map ( d ) are compared to FLAIR ( a ), T1w contrast‐enhanced MRI ( b ), an ADC map ( e ), and perfusion‐weighted imaging ( f ). Reproduced from Springer et al 2022 under CC license 112 …”
Section: Resultsmentioning
confidence: 99%
“…MRF-basierte T1- und T2-Relaxometrien konnten dabei bereits erfolgreich Tumorgrade und IDH-Status unterscheiden ( Abb. 6 ) 12 – und auch Parkinson erkrankte Patienten von Gesunden 13 . Das Besondere des MR-Fingerprinting ist, dass die Sequenzen zumindest in der Theorie „sensibilisiert“ werden können für Gewebeeigenschaften wie Perfusion und den Eiweißgehalt, wie er z.…”
Section: Akquisitionsbasierte Mrt-verfahrenunclassified